COMBO DEL ICE EN EL MOMENTO CULMINANTE DE LAS PROTESTAS SONDEO TELEFÓNICO 24-25 DE MARZO DEL 20001 - Campos Ramírez, Domingo (2023)
This article reports on public opinions in relation to a legal reform of the electricity and telecommunication state-owned compan, as well as the sector in general. The opposition to this legal reform generated a widespread protest movement, the largest in the last fifty years. The survey took place at the height of the mobilization. It touches on positions, motivations, information and behavior.